PENGARUH PEMBERIAN EDUKASI PADA PENGETAHUAN PENGGUNAAN ANALGESIK NYERI NEUROPATIK DAN DISMINORE DI DESA KUANYAR, MAYONG, JEPARA - Meliana Erianti; Ria Etikasari; Intan A. Rosnarita (Nusantara Hasana Journal, 2026)
One example of self-medication issues is the differing treatment needs between neuropathic pain (requiring non-analgesic adjuvant medications) and dysmenorrhea (susceptibility to the risk of NSAID side effects due to excessive doses). This study aimed to analyze a comprehensive profile of the knowledge of the Kuanyar Village community regarding the use of analgesics for neuropathic pain and dysmenorrhea. This study employed a quantitative descriptive design through a cross-sectional survey. Data were collected using a structured questionnaire to calculate respondents' knowledge scores, drawn through a purposive sampling technique. The results showed were predominantly female (52%), with 41.2% aged 21-35 years, 60% having a high school education, 35% being self-employed, 45% earning between 1 million and 3 million rupiah, and 42.5% being involved in community organizations. The level of knowledge fell into three categories before the education: poor and sufficient same about (30%) and good (40%). After the education through printed media, the level of knowledge changed sharply, with the poor level of knowledge decreasing sharply, as did the sufficient and good categories, each at 6% and 94%, respectively. This was supported by the analysis results using the Wilcoxon test with a significance value of 0.000 <0.05.